Exploring LEGO Mindstorms EV3 tools and techniques for building and programming robots - Park, Eun Jung (John Wiley & Sons, Inc., 2014)
The essential guide to building and programming LEGO EV3 interactive robots Exploring LEGO Mindstorms: Tools and Techniques for Building and Programming Robots is the complete guide to getting the most out of your LEGO Mindstorms EV3